Third-party employer branding - SAINI, Mukta G. (Institutional Knowledge at Singapore Management University, 2023)
There has been a growing interest in third-party employment branding (TPEB) because prospective and current employees perceive it more credible than the company-controlled employer branding. The academic research on TPEB has also been rapidly growing. This chapter reviews the TPEB research using a bibliometric analysis of 734 articles published between 1996 and 2021. The analysis shows that 'employer branding,' 'recruitment,' 'Glassdoor,' and 'word-of-mouth' are the major keywords in this domain. TPEB research can be grouped into three themes – (i) ‘best employer status and its outcomes’, (ii) ‘antecedents and consequences of third-party employment branding’, and (iii) ‘word-of-mouth and recruitment’. We propose directions for future research in these three areas. Additionally, we recommend further research in the areas such as influence of TPEB on financial metrics, effect of negative TPEB information on companies, counter-productive effects of best employer surveys, inclusiveness of best employer surveys and cross-fertilization between research on employer branding, internal branding, and TPEB.